2001
DOI: 10.1106/3g5k-c6c2-gl8f-bjj4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cigarette Variables on Ignition Propensity of Various Fabrics

Abstract: A factorial matrix consisting of 25 cigarette samples, where tobacco density, circumference, paper porosity and paper citrate were varied at three levels was tested on cotton duck, treated sailcloth and four commercial fabrics. Duck fabrics are heavy canvas-type fabrics that have very high levels of potassium ions. Treated sailcloth is a light areal density fabric treated with potassium sulfate and hydroxide salts to produce ignition results that mimic those obtained with light areal density commercial fabrics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The time and heat flux required for the initiation of smouldering was also found to depend on the environment and the properties of the fabric (Kellogg et al 1998;Yi et al 2001). However, different results were obtained by different test laboratories as to the degree of correlation with cigarette type, and up to three quarter of the 79 upholstery fabrics produced similar ranking with the cotton duck fabrics used Eberhardt et al 1997;Hirschler 1997aHirschler , 1997bWanna & Zelius 2001;Wanna & Chen 2001;Ihrig et al 1987). Taken together, these studies highlight the technical difficulties in developing a fabric-based standard method due to the specification and production of reproducible batches of test fabrics.…”
Section: Fabric and Substrate Parametersmentioning
confidence: 97%
“…The time and heat flux required for the initiation of smouldering was also found to depend on the environment and the properties of the fabric (Kellogg et al 1998;Yi et al 2001). However, different results were obtained by different test laboratories as to the degree of correlation with cigarette type, and up to three quarter of the 79 upholstery fabrics produced similar ranking with the cotton duck fabrics used Eberhardt et al 1997;Hirschler 1997aHirschler , 1997bWanna & Zelius 2001;Wanna & Chen 2001;Ihrig et al 1987). Taken together, these studies highlight the technical difficulties in developing a fabric-based standard method due to the specification and production of reproducible batches of test fabrics.…”
Section: Fabric and Substrate Parametersmentioning
confidence: 97%
“…The smouldering behavior of cigarettes on substrates is different from that of cigarettes burning in air [19]. The type of cigarette and the burning rate of the cigarette can also have an effect [39,40]. Light density fabrics (e.g.…”
Section: Cigarette Smouldering Ignitionmentioning
confidence: 99%
“…sailcloth) can have high ignitions with fast smouldering cigarettes, while heavy density fabrics (e.g. cotton duck) can have high ignitions with slow smouldering cigarettes [40,41]. Gann et al [42,43] showed that cigarettes can be modified (some combination of reduced tobacco packing density, less porous paper, smaller cigarette circumference and no citrate [burn additive] in the paper) to have a lower relative ignition propensity than conventional cigarettes.…”
Section: Cigarette Smouldering Ignitionmentioning
confidence: 99%